2007
DOI: 10.1097/ico.0b013e31802b4201
|View full text |Cite
|
Sign up to set email alerts
|

Unique Homologous siRNA Blocks Hypoxia-Induced VEGF Upregulation in Human Corneal Cells and Inhibits and Regresses Murine Corneal Neovascularization

Abstract: AMT helps in ocular surface reconstruction, promotes rapid epithelial healing and partially restores limbal stem cell function. It can be considered as an effective modality for the ocular surface restoration in chemical and thermal injuries in selected cases. Success rates in acute and chronic cases are comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 25 publications
1
48
0
3
Order By: Relevance
“…Each cohort consisted of 8-10 mice. Animals healing and reduce scarring (31). A recent study investigating the effects of a mixed cell population consisting were culled 4 weeks after commencing the experiment and blood and liver tissue collected.…”
Section: Introductionmentioning
confidence: 99%
“…Each cohort consisted of 8-10 mice. Animals healing and reduce scarring (31). A recent study investigating the effects of a mixed cell population consisting were culled 4 weeks after commencing the experiment and blood and liver tissue collected.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of this new biomaterial may be because the HAM promotes epithelialization and neovascularization and possesses immune privilege (Sippel et al 2001). It has been previously documented that HAMs may accelerate epithelialization of gingival wounds and ocular chemical and thermal injures when reconstructing damaged organs and corneal tissue (Rinastiti et al 2006;Madhira et al 2008;Sangwan et al 2007;Tejwani et al 2007). Also, Santos et al (2005) have demonstrated the suitability of HAMs for treating limbal stem cell deficiency (LSCD).…”
Section: Discussionmentioning
confidence: 96%
“…The largest size possible, allowing closure of eyelids, is preferable in order to prevent adhesions and shortening of the fornices without touching the cornea (4) . Several studies have reported successful treatment of ocular burns using AMT with or without limbal cell transplantation (13)(14)(15)(16)(17)(18) . AMT alone was reported to be efficient in terms of restoring ocular surfaces in cases of mild to moderate burns (14,16) .…”
Section: Discussionmentioning
confidence: 99%